Zwischen den Welten: zur kognitiven und kommunikativen Ko-Konstruktion von Alteritätserfahrung - Schröder , Ulrike (Linguistik Online, 2020)
It is still hard to find the examination of real interaction from a cognitive, “embodied” and multimodal perspective in empirical practice, concurrently maintaining the operational framework of conversation analysis. The following article aims at showing how co-participants in talk-in-interaction co-construct intercultural experience multimodally, that is, on verbal, prosodic and gestural-corporal levels. Based on five sequences taken from the ICMI corpus of the research group Intercultural Communication in Multimodal Interactions, founded at the Federal University of Minas Gerais in 2010, it will be revealed how interactants narrate their intercultural experience based on reenactments, how (inter)cultural conceptualizations are (co-)built by means of iconic, metaphorical and beat gestures, by gaze, posture and body movements, as well as by prosodic cues such as pitch jumps and contours, accents, volume and tempo. Concurrently, all those means serve as contextualization cues to express the interlocutors’ involvement, stance, alignment as well as affiliation, and can be conceived as “points of access” to deeper entrenched schemata related to the participant’s (inter)cultural experiences. In this sense, the study aims to bridge the gap between conversational and interactional linguistics, on the one hand, and cognitive and cultural linguistics, on the other.